Синтез нелінійних полічастотних вібраційних машин з резонансними режимами роботи - Гурський, Володимир Миколайович (Національний університет "Львівська політехніка", 2018)
У дисертаційній роботі вирішено актуальну науково-прикладну проблему машинознавства – розроблення узагальненого методологічного підходу, що охоплює питання синтезу пружно-інерційних, силових параметрів і частотних характеристик полічастотних вібраційних систем для забезпечення резонансних режимів роботи та підвищення ефективності їх функціонування. Обґрунтовано використання імпульсного (однотактного) електромагнітного приводу для реалізації двочастотних і віброударних машин визначеної структури та технологічного призначення. Розроблено розрахунковий алгоритм синтезу пружно-силових параметрів вібраційних систем із кусково-лінійними пружними характеристиками. Для спрощення процедури синтезу запроваджено два коефіцієнти, що входять у вирази для власних частот коливань. Реалізовано віброударні системи підвищеної ефективності функціонування, що за показником енергетичної ефективності функціонування переважають класичні гармонійні резонансні системи в 2 рази, віброударні в 3 рази. Запроваджено розрахункові формули для модернізації існуючих гармонійних машин у двочастотні. Розглянуто завдання забезпечення динамічної жорсткості конструкцій робочих органів з їх оптимізацією за частотно-масовим показником. Для реалізації віброударних систем запропоновано та обґрунтовано перевіркою міцності схему з однією плоскою пружиною та двома проміжними полімерно-металевими циліндричними опорами. Визначальні положення щодо підвищення ефективності функціонування на основі розробленої методології синтезу параметрів підтверджено на практиці. В диссертационной работе решена актуальная научно-прикладная проблема машиноведения – разработка обобщенного методологического подхода, охватывающего вопросы синтеза упруго-инерционных, силовых параметров и частотных характеристик поличастотных вибрационных систем для обеспечения резонансных режимов работы и повышения эффективности их функционирования. Обосновано использование импульсного (однотактного) электромагнитного приводу для реализации двухчастотных и виброударных машин определенной структуры и технологического назначения. Разработан расчетный алгоритм оптимизационного синтеза упруго-силовых параметров вибрационных систем с кусочно-линейными упругими характеристиками. Для упрощения процедуры синтеза введены два коэффициента, входящих в выражения для собственных частот колебаний. Реализовано виброударные системы повышенной эффективности функционирования, что по показателю энергетической эффективности функционирования преобладают классические гармоничные резонансные системы в 2 раза, виброударные в 3 раза. Одержаны расчетные формулы для модернизации гармоничных машин в двухчастотные. Рассмотрены задачи обеспечения динамической жесткости конструкций рабочих органов с их оптимизацией по частотно-массовому показателю. Для реализации виброударных систем предложено и обосновано проверкой прочности схему с одной плоской пружиной и двумя промежуточными полимерно-металлическими цилиндрическими опорами. Определяющие положение по повышению эффективности функционирования на основе разработанной методологии синтеза параметров подтверждено на практике. The purpose of the presented research consists development of a generalized methodological approach, covering issues of synthesis of elastic-inertial, power parameters and frequency characteristics of multi-frequency vibration systems for providing resonant operating modes and increasing the efficiency of their functioning. The substantiation of the expediency of using the implemented poly-frequency pulsed vibratory systems is made using the comparative analysis according to the established criterions. The classification of schemes of power supply of electromagnetic vibrators, the scopes of usage and technical characteristics of industrial vibrators are presented in Chapter I. The differential equations of the basic power and energy characteristics of the electromagnetic circuit of vibration exciters are given for different connection diagrams. The features of using the pulsed (single-cycle) power supply schemes in vibratory machines are defined. The structural schemes of the poly-frequency systems (linear two-frequency and nonlinear vibro-impact), as well as the means of implementation of the relevant modes, structural and dynamic features, are considered. The criterions of integrated (technological and power) operational efficiency assessment of a wide class of vibratory systems of technological purpose are defined in order to carry out the further optimization synthesis and comparative dynamic analysis. Chapter II is devoted to the problems of synthesis of the two-frequency resonant operation modes of the three-mass vibratory machines. In particular, the formulas for determination of the multiple two-frequency resonant mode are defined by calculation of elastic parameters. The problems of synthesis of the two-frequency resonant systems are considered, the assessment of their operation and implementation of the modes with the corresponding harmonic composition of the working mass acceleration are carried out. The problem of synthesis and dynamic analysis of the two-frequency resonant systems is solved by means of modernization of harmonic machines. The defining approaches for carrying out the dynamic analysis of nonlinear models of the resonant vibratory machines are presented in Chapter IІІ. For this purpose, the corresponding algorithms are developed on the basis of the integral numerical methods of analysis of the systems of nonlinear differential equations of the second order. The problems of determination of the equations of skeletal (constructional) curves of vibro-impact systems based on the asymmetric piecewise linear elastic characteristics in two-mass systems are considered. Chapter III also deals with the combined problems of optimization synthesis and dynamic analysis of vibro-impact resonant systems with electromagnetic drive. The fundamental time and amplitude-frequency dependences of systems with different types of piecewise-linear elastic characteristics are constructed, the assessment criteria are defined and the multi-criteria analysis of the synthesized systems is carried out. It is necessary to mention that the presented non-linear models have been solved using the numerical methods of “Radau”, “BDF”, “Adams”, “AdamsBDF” (for “nonslack” differential equations and their systems) taking into account the availability of the impulse conditions in electromagnetic and mechanical circuits of the vibro-impact systems. The comparative analysis of the optimal vibro-impact systems obtained as a result of modernization of harmonic machines is carried out. The vibro-impact multi-mode systems operating at the major and at the subharmonic resonance are synthesized. The additional energy and technological advantages of operation of the vibro-impact system, which implements the super-resonance oscillations, are detected. The mathematical formulation of the vibro-impact system by the equations of Hill and Mathieu type is presented. The analysis of dynamic stability of the solution for the major harmonic is carried out using the Mathieu's chart. In addition, the comparative analysis of the obtained solutions is considered by the method of Bubnov-Galerkin taking into account the number of harmonics determined on the basis of the Pearson's convergence criterion. This allows to select the desired number of harmonics, which is taken in the found solutions. The parametric synthesis of the three-mass vibro-impact systems with additional restrictions on the inertness of the reactive mass and with kinematic constraints is carried out. Their advantages over two-mass vibro-impact systems by the energy criterion are defined. In general, a generalization of the resonant systems in terms of the multi-criteria analysis and parametric synthesis is carried out. The corresponding quantitative indexes of the comparative efficiency are obtained. Chapter IV is formed on the basis of the optimization problems, which deal with the purpose to ensure high dynamic stiffness (stability) and to reduce the weight of structural elements of vibratory machines. For this purpose, the frequency-mass criterion is additionally introduced. It is expedient to use the proposed frequency-mass criterion in order to perform the refined selection of the optimal parameters of complicated engineering structures (working elements of machines, rod systems with discrete and distributed parameters, frames, etc.), which should be previously designed and analyzed using the applied CAE-systems of the corresponding software (SolidWorks, Inventor, Ansys, etc.). The use of a single flat spring for the implementation of asymmetric elastic characteristics with rigid and compliant intermediate supports is substantiated by force and frequency analysis. The strength and durability analysis of the flat spring is carried out taking into account the operation conditions of the rod vibro-impact system. The applied investigations and developments on the subject of the studied vibratory systems are presented in Chapter V. The 3D-models of vibro-impact systems and two-frequency machines are designed. Their mathematical modeling and evaluation of the operation efficiency are carried out. The results of experimental investigations of the vibro-impact two-mass module with pulsed electromagnetic drive are presented. The basic scientific accomplishments and indexes of operation efficiency of the vibration systems being evaluated are elucidated in generalizations. The features and expediency of use of the energy and technological parameters when performing the comparative analysis of harmonic and vibro-impact machines are defined.
Синтез нелинейных поличастотных вибрационных машин с резонансными режимами работы
Synthesis of the nonlinear poly-frequency vibratory machines with resonance modes
Keywords: резонанс; віброудар; електромагнітний привод; полічастотні коливання; синтез; оптимізація; динаміка; резонанс; виброудар; электромагнитный привод; поличастотных колебания; синтез; оптимизация; динамика; resonance; vibro-impact; electromagnetic drive; poly-frequency oscillations; synthesis; optimization; dynamics; 621.01